Q1a3a native-American Y-haplogroup detection in DNA quantification step: A quick diagnosis for Y-chromosome database selection - Ginart, Santiago (2019)
We present the optimization of a previously developed DNA quantification approach that now makes possible the simultaneous detection of Q1a3a Native-American Y-chromosome haplogroup by means of real time-PCR followed by high resolution melting (HRM) analysis. Genotyping is possible by differences in melting temperature (Tm) of one specific Y-chromosome fragment (58bp long, included in the reaction cocktail) which contains the M3-Q3 C/T polymorphism. The specific variant M3-Q3/T (Native-American lineage) has a Tm ≈ 76 °C, whereas M3-Q3/C (non-Native-American) has Tm ≈ 77 °C. Fifty reference male DNA samples (blood and muscle from autopsy) were analyzed. DNA concentration ranged from 0,01 to 28 ng/μL. Thirteen showed Native-American signature (TmT = 76,02 ± 0,04) while thirty-seven as non-Native-American (TmC = 77,13 ± 0,06). These results were compared to those predicted from Y-STRs by White Athey´s on-line software. Casework samples containing male DNA were quantified and successfully haplogrouped. The STRs profiles, subsequently obtained, correlated well with quantitation results. This system represents an approach that provides valuable information at early stages of genotyping process, and useful for choosing the most suitable Y-chromosome database for statistical evaluations.